Technology adoption in franchising business: Understanding factors and challenges - Nur Nabila Huda, Sabaran; Nurul Ashykin, Abd Aziz (Universiti Utara Malaysia, 2023)
In today's era, franchising is a widely adopted business model used by companies to expand domestically and internationally. Undoubtedly, technology serves as the backbone for efficient management of day-to-day operations in franchise outlets. This paper aims to offer a general overview of technology integration in franchise business, providing an initial understanding. Our research involved a review of previous studies on franchising that included technological adaptation. The focus of this paper is to increase the understanding of the use of technology in franchise businesses, addressing the factors and challenges faced by franchise businesses seeking technology integration. The review method was used to explore this topic more deeply. Factors have been discussed where it explains what the purpose of the franchise business is to adopt technology and how it helps operations. In addition, challenges are also explained where they are related to what these franchise businesses are facing in maintaining the adoption of the technology they use in a competitive market. Finally, this study identifies future research directions that can be a guide for both future studies and industry players involved in franchise development.